An integrated mixed refrigeration cycle for pre-cooling of refrigeration below 25 K. (April 2019) - Kloeppel, S; Quack, H; Haberstroh, C
Abstract: Two trends can be found in current large-scale cryogenic projects. The first is the ever-increasing capacity requirements, while also a shift towards cooling demands at higher temperatures is observed. Conventional helium cycles require the use of oil flooded screw compressors, which are limited in efficiency, capacity, and reliability. Reverse-Brayton cycles with neon-helium mixtures deliver efficient refrigeration at a temperature above the dew point of neon, but cannot be applied to the cooling of conventional superconductors. This paper describes an approach where oxygen as a heavier gas allows the use of turbo-compressors viable. The oxygen is separated and used for providing refrigeration at higher temperature levels.